PHILOSOPHICAL FOUNDATIONS OF INTEGRATING ECOLOGICAL AND AESTHETIC EDUCATION - Azimov Ozod Mamatkulovich (Bright Mind Publishing, 2025)
This article provides a comprehensive philosophical exploration of the integration of ecological and aesthetic education. The objective is to examine both the theoretical and practical dimensions of merging these two educational paradigms and to demonstrate how such integration fosters an eco-aesthetic ideal within the consciousness of younger generations. The study emphasizes the philosophical necessity of uniting ecological responsibility with aesthetic sensitivity, arguing that both dimensions are interdependent in shaping holistic human development. Ecological education cultivates respect for nature and sustainability, while aesthetic education fosters appreciation for beauty and artistic creativity. Together, they provide a foundation for building responsible, creative, and socially conscious individuals. The article analyzes philosophical theories of value, the ethics of responsibility, and cultural aesthetics to reveal the underlying principles of eco-aesthetic integration. It also discusses pedagogical strategies that apply these principles in practice. The integration of ecological and aesthetic values not only strengthens youth awareness of environmental issues but also promotes spiritual enrichment and artistic creativity, ensuring harmony between humanity, nature, and culture. This dual approach addresses contemporary global crises by preparing young people to act as agents of sustainable and culturally enriched development.
Keywords: Ecological education, aesthetic education, integration, philosophical approach, eco-aesthetic ideal, environmental responsibility, cultural aesthetics, youth development.